THE ROLE OF SOCIAL CAPITAL IN IMPROVING THE DYNAMICS OF FARMER GROUPS - Sri Subekti; Mudiyono Mudiyono; Sri Peni Wastutiningsih (UNEJ e-Proceeding, 2012)
Social capital is social energy in a community used to actuate a farmer group to be more dynamic to gain an end. Social capital cannot be formed by farmers individually, but it extremely depends on farmer group’s capacity and government to build trust, norms and social networks. Qualitative method is used in this research. The data collection is completed by using triangulation including non-participant observation, interview in depth,and documentation. The approach used is a case study that is to study the role of social capital in improving the dynamics of the Orange farmer group Sidomulyo IV, Sidomulyo village, Umbulsari subdistrict, Jember regency. The study results show that the members’ trust toward the farmer group Sidomulyo IV motivates their members to work together and to actively participate in the community’s activities to achieve their goals, so that their group becomes more dynamic. Cooperation creates the norms for the farmer group including the meeting schedule, the cash collection, the facility utilization, government help administration, and pest and disease management. It also builds social networks to fulfill the members’ needs involving the official kiosks of production utilities, gapoktan (farmer group alliance), government, Orange traders, and Hippa (association of waterusing farmers). Counseling activity through SL program (field school) also can increase farmer group’s social capital.